Students' Perceptions of Collaborative Learning in English for Medical Purposes (EMP) Course - Meisani, Diah Royani; Hidayati, Laely (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Research on collaborative learning in English for Specific Purposes (ESP), particularly from the students’ perspectives, remains relatively limited due to prevailing focuses on teacher-centered approaches and individual assessment. The present study addresses the gap by exploring how collaborative learning impacts student engagement and outcomes in an English Medical Purposes (EMP) course. A total of 328 Medicine, Nursing, and Nutrition students completed a questionnaire using a 5-point Likert scale to evaluate their perspectives on collaborative learning. Results show overall satisfaction, with mean ratings ranging from 4.00 to 4.25 across key aspects such as utility, alignment with expectations, enjoyment, practical application, sense of community, exchange of ideas, and skill development. These findings underscore the value of collaborative learning in fostering active participation and supportive learning environments. In addition, as the identification of potential weaknesses in current implementations of collaborative learning in EMP contexts was not explored, future research should investigate the challenges and develop targeted strategies to optimize collaborative learning experiences in EMP settings.